Scandinavian Object Shift and Optimality Theory - Engels, Eva.; Vikner, Sten.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
This book presents an account of object shift, a word order phenomenon found in most of the Scandinavian languages where an object occurs unexpectedly to the left and not to the right of a sentential adverbial. With new and original observations, it is an important addition to the fields of phonology, optimality theory and theoretical syntax.
Keywords: Linguistics; Grammar; Scandinavian languages; Syntax; Linguistic change; Linguistics; Syntax; Language Change; Grammar; Scandinavian